STRENGTHENING MICRO, SMALL, AND MEDIUM ENTERPRISES DIGITAL MARKETING BASED ON LOCAL COMMUNITY EMPOWERMENT TO SUPPORT THE REALIZATION OF SDG’S IN SUCOLOR VILLAGE - Prihandini, Rafiantika Megahnia; Adawiyah, Robiatul; Setiawanai, Susi; Dewi, Mayra Fadhilla (As-Sidanah, 2025)
Sucolor Village possesses significant local economic potential, particularly in the Micro, Small, and Medium Enterprises (UMKM) sector. However, the utilization of digital technology for product marketing remains limited, resulting in restricted market access and low competitiveness of local products. This activity aims to optimize digital marketing strategies based on local community development to support UMKM sustainability and contribute to the achievement of the Sustainable Development Goals (SDGs) in Sucolor Village. The method employed in this initiative is the ADDIE training model, which includes digital marketing training, branding optimization, and marketing strategies based on social media and e-commerce. This activity involves empowering the local community, particularly women and youth groups, to enhance digital skills and product innovation. As a result of this program, participants demonstrated significant improvement in digital marketing competence, with average post-training scores increasing from 1.7-2.3 to 3.9-4.3 across key indicators such as branding, content creation, and marketplace management. A digital catalog website was successfully developed, and local UMKM began actively promoting their products online. Additionally, the introduction of coffee-themed batik products reinforced local identity and broadened the creative economy. Overall, this community service proved to be an effective way to enhance digital literacy, expand market reach, and increase the economic resilience of rural entrepreneurs.